2014
DOI: 10.1016/j.jval.2014.08.1423
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Of Dabigatran Compared With Warfarin, Apixaban, Rivaroxaban And Low Molecular Weight Heparins For The Treatment And Secondary Prevention Of Venous Thromboembolism In Colombia

Abstract: clinical response to treatment and the number of QALYs per patient accrued during the study. Only direct medical costs (drug acquisition, administration and hospitalization costs) were incorporated in the model, as the analysis was conducted from a third-party payer perspective. With respect to administration cost, two alternative scenarios were considered in the base case analysis: administration in day-case unit and administration in the hospital outpatient department. Probabilistic sensitivity analysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…43 Currently, rivaroxaban is the most commonly used DOAC, followed by dabigatran and apixaban. A cost‒benefit analysis 44 showed that the treatment with DOACs resulted in fewer deaths due to bleeding, with 5 for dabigatran, 7 for apixaban, 7 for rivaroxaban, 9 for LMWH, and 15 for warfarin, per 10,000 patients. It was also demonstrated that DOACs incur lower costs than LMWH in prevention and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…43 Currently, rivaroxaban is the most commonly used DOAC, followed by dabigatran and apixaban. A cost‒benefit analysis 44 showed that the treatment with DOACs resulted in fewer deaths due to bleeding, with 5 for dabigatran, 7 for apixaban, 7 for rivaroxaban, 9 for LMWH, and 15 for warfarin, per 10,000 patients. It was also demonstrated that DOACs incur lower costs than LMWH in prevention and treatment.…”
Section: Discussionmentioning
confidence: 99%